Nutritional quality and feasibility of meals provided by a canteen for the poor: the 60-year experience of the “Opera di San Francesco” in Milan, Italy - Maioli, Claudio; Muzio, Fulvio; Cioni, Federico; Porrini, Marisa; Maioli, Giuditta; Riso, Patrizia (Progress in Nutrition, 2022)
The rapid increase in the number of vulnerable people who depends on meals provided by the canteens for the poor all over the world suggests the importance to provide adequate menus Objectives: to present a dining experience for the poor and/or homeless in Milan by analyzing: 1) the general characteristics of the canteen users 2) the nutritional composition of the meals with the aim of highlighting possible nutritional deficiencies 3) the feasibility aspects associated to the menu development and management Setting: Canteen for the poor “Opera di San Francesco” Milan, Italy Methods: A qualitative and quantitative analysis of the cost, type of foods and nutrients composition of the overall meals provided (736.352) was made and data compared with the reference values ​​for the adult Italian population (LARN 2014). The canteen distributes about 2,336 meals a day, 6 days a week from Monday to Saturday. The menus analysed were those of the winter (7 months, from 01/01 to 30/4 and from 01/10 to 31/12) and summer (5 months, from 1/5 to 30/09) seasons. The total number of meals in the period 2017-2020 was also considered. Results: On average, the winter menu provided 2039 Kcal as a mean (15% proteins, 29% lipids, 56% carbohydrates) while the summer menu provided 2146 Kcal (15% proteins, 28% lipids, 57% carbohydrates). The total number of meals provided remained constant in the period 2017-2020 despite the sanitary situation. Discussion: Overall, energy intake and macronutrients composition of both the summer and the winter menus were in line with recommendations. However, calcium, vitamin D, folate, vitamin B2, B6, B12 and zinc requirements were not satisfied due to the scarcity of foods such as milk and dairy products but also fish and vegetables while the salt content was high with respect to recommendations.